The Dutch Reformed Church in the Victoria circle: Chibi circuit, Mashonaland, 1874-1956 - Mazarire, Gerald C. (2016)
The Berlin Missionary Society (BMS) established Chibi Mission Station in Chivi (Mashonaland, Rhodesia, present-dayZimbabwe) in 1894, but this station was taken over by the Dutch Reformed Church (DRC) in 1907. This paper argues that the DRC take over of the BMS establishments was a turning point in the missionary history of the Victoria district characterized by a phenomenal expansion of preaching centres and a wide network of 'kraal schools'. However, signs of fatigue in the Christian educated class in Chivi were already creeping in in the mid-1920s, when Andreas Pedzisai Shoko, a product of the DRC mission schools, founded one of the biggest independent churches in Zimbabwe, the Zion Apostolic Faith Mission or Zion yeNdaza. It was a combination of the rise of Independent African Christianity and the growing competition amongst different Christian denominations (particularly the Roman Catholic Church, RCC) seeking to expand that ultimately brought an end to DRC monopoly in the 1950s.